Searching for Purpose: Mezirow’s Early View of Transformative Learning - Amy D. Rose (Adult Education Research Conference, 2015)
This paper discusses the early work of Jack Mezirow in terms of his later writings on transformative learning. In particular, it examines his early interest in the ways individuals change through education and how this related to broader social change. It also posits that his earlier interest was philosophical rather than based in learning theory.
Keywords: Mezirow; Transformative Learning; adult education philosophy